High performance wireless wearable technologies for sports training and tele-health - Mediana (2015)
With the recent advances of technology in wireless communication, sensors, and low power integrated-circuit, Wireless Body Sensor Network (WBSN) has emerged. It has been used in a wide range of applications like healthcare monitoring, sports training, and wellness. However, WBSN poses several issues like scalability, reliability, packet delay due to body blockage, movement and dense deployment. Therefore, an efficient routing scheme is essential to achieve good network performance. This paper presents the performance study of Backpressure Collection Protocol (BCP), a new alternative of data collection protocol that routes packet on a per-packet basis dynamically using congestion gradient, for WBSN. The study consists of evaluating the packet delivery ratio (PDR), packet loss, and end-to-end packet transmission delay for a single-hop and two-hop communication networks using BCP. The experiment results showed BCP performs excellent in WBSN with PDR approximately being 1 and packet loss being zero after 5 seconds booting up, and packet delay on average being 13 milliseconds. The Last-In-First-Out (LIFO) mechanism implemented in BCP appears to be also suitable for health-care monitoring application because the most recent sensing data is sent to base station instead of outdated data. Besides, this paper has demonstrated packet loss optimization to reduce the packet loss during the initial 5 seconds booting to zero packets.